Physicochemical, nutritional and functional properties of Annona muricata fruit puree and juice - AMOUSSOU EPSE FAGLA, A. BALBINE; HOUNDJI, BIDOSSESSI VICTOR SATURNIN; Novidzro, Kosi Mawuéna; DOSSOU, JOSEPH (My University, 2019)
This work had been made to determine the physicochemical, nutritional and functional properties of Annona muricatafruit puree and juice. Nine lots of juice were producedThe batches differ from each other by the pH or the dilution rate of the puree. The pH values of the types of juice produced were 3; 3.5 and 4.5; the dilution rate (water/mash) are 50/50, 60/40 and 33.33/66.66. Only the puree went under the physicochemical, nutritional and functional analyzes and as for the juice, the pH, titratable acidity, soluble sugar content and dry matter were the parameters evaluated. The characterization of the puree showed that it was pasty, sweet and acidic with a pH of 4.45 ± 0.1, a consistency of 18 ± 0.0 cm / 30s and a Brix degree of 10.5 ± 0.2. As for the physicochemical composition, the results showed that this puree contains 80% water and the composition per 100 g of mash gives glucose contents of 17.95 ± 0.05 g, proteins of 1.1 ± 0.01 g and lipids of 0.00 g. The functional properties revealed that this mash has an antioxidant capacity (IC50 = 18.97 ± 0.46 ppm), with a total polyphenol content of 141.24 ± 0.14 mg-eq/100 g, a tannin content of 0.22 ± 0.03 geq/100 g, and a vitamin C rate of 1.66 ± 0.02%. However, the mash is devoid of anthocyanins. The analysis of the juicerevealed that the soluble sugar content varied from 3 to 5ºBx, the titratable acidity from 0.486% to 0.729% and the dry matter from 1.942% to 5.360%. The juice and particularly the puree studied are therefore rich in nutrients with interesting functional properties. Puree, acidic, pasty and consistent, with its antioxidant activity could then be an interesting food.